1999
DOI: 10.1046/j.1464-410x.1999.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary in situ extracorporeal shock wave lithotripsy in the management of ureteric calculi: results with a third‐generation lithotripter

Abstract: Objective To review the results of primary in situ cations. Stone-free rates were 90% for upper ureteric, 89% for middle-third and 86% for lower-third calculi. extracorporeal shock wave lithotripsy (ESWL) for the treatment of ureteric stones using a third-generation Twenty-one patients required auxiliary procedures in the form of JJ stenting or nephrostomy. Failure of lithotripter, the Dornier MFL 5000 (Dornier Medizentechnic, Germany).ESWL was associated with stone size (>1.3 cm) but not location or inadequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 14 publications
(15 reference statements)
2
22
1
1
Order By: Relevance
“…In addition, other studies correlated treatment failure with ESWL voltage and stone composition, but not location or inadequate treatment. 3,8,9 A subgroup of calculi less likely to succeed could thus be identified: calculi >1 cm 2 , with severe uropathy and functional annulment or delay. The major disadvantages of ESWL are the number of repetitions often required, and the long wait until the last fragment is passed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other studies correlated treatment failure with ESWL voltage and stone composition, but not location or inadequate treatment. 3,8,9 A subgroup of calculi less likely to succeed could thus be identified: calculi >1 cm 2 , with severe uropathy and functional annulment or delay. The major disadvantages of ESWL are the number of repetitions often required, and the long wait until the last fragment is passed.…”
Section: Discussionmentioning
confidence: 99%
“…It is highest in the distal ureter, with lesser success in the middle and proximal ureter in that order. 8,10 Although URS with holmium laser lithotripsy achieves excellent results for proximal ureteral stones 1 cm or larger, ESWL is equally efficient for stones less than 1 cm. 11 The consensus is that ESWL therapy should remain a first-line choice in upper ureteral stones, especially if it is less than 1 cm, keeping other modalities for unfragmented stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birçok çalışmada %80-%90 başarı oranı rapor edilmiş ve üreter taşlarının tedavisinde ilk tedavi seçeneği olabileceği vurgulanmıştır (2)(3)(4). Bu çalışmada, kliniğimizde Ocak 2013-Ocak 2014 tarihleri arasında proksimal üreter taşı olup ESWL tedavisi uygulanan 96 olguda sonuçlarımız geriye dönük olarak incelenmiş ve literatür eşliğinde tartışılmıştır.…”
Section: Introductionunclassified
“…It become a safe and accepted method of treatment for urinary tract stones and in 1984 was approved by FDA [19][20][21] . It has been recommended as a first-line treatment for mid ureteric calculi in several studies and reported 80-90% success rate 1,19,[23][24][25] . It is a standardized procedure which results in stone free rates depend on the size, composition and the location of the stone as well as the type of the lithotripter 1,26,27 .…”
mentioning
confidence: 99%